Measuring acceleration and deceleration in soccer-specific movements using a local Position Measurement (LPM) System - Stevens, T. G. A.; de Ruiter, C. J.; van Niel, C.; van de Rhee, R.; Beek, P. J.; Savelsbergh, G. J. P. (International Journal of Sports Physiology and Performance, 2014)
Purpose: A local position measurement (LPM) system can accurately track the distance covered and the average speed of whole-body movements. However, for the quantification of a soccer player`s workload, accelerations rather than positions or speeds are essential. The main purpose of the current study was therefore to determine the accuracy of LPM in measuring average and peak accelerations for a broad range of (maximal) soccerspecific movements. Methods: Twelve male amateur soccer players performed 8 movements (categorized in straight runs and runs involving a sudden change in direction of 90° or 180°) at 3 intensities (jog, submaximal, maximal). Position-related parameters recorded with LPM were compared with Vicon motion-analysis data sampled at 100 Hz. The differences between LPM and Vicon data were expressed as percentage of the Vicon data. Results: LPM provided reasonably accurate measurements for distance, average speed, and peak speed (differences within 2% across all movements and intensities). For average acceleration and deceleration, absolute bias and 95% limits of agreement were 0.01 ± 0.36 m/s2 and 0.02 ± 0.38 m/s2, respectively. On average, peak acceleration was overestimated (0.48 ± 1.27 m/s2) by LPM, while peak deceleration was underestimated (0.32 ± 1.17 m/s2). Conclusion: LPM accuracy appears acceptable for most measurements of average acceleration and deceleration, but for peak acceleration and deceleration accuracy is limited. However, when these error margins are kept in mind, the system may be used in practice for quantifying average accelerations and parameters such as summed accelerations or time spent in acceleration zones.